Employee Acceptance of Use: A Precondition for Enhancing Therapy Effectiveness, Patient Safety, and Economic Efficiency - von Eiff, Maximilian C.; von Eiff, Wilfried; Roth, Andreas; Ghanem, Mohamed (Frontiers in Public Health, 2019)
Background From workplace engineering sciences it is confessed that work efficiency (measured by the criteria efficiency and effectiveness of therapy, economy, patient safety) is dominantly determined by staff acceptance of new technology and reengineered workflows. So, it was intended to ascertain and assess differences in terms of the acceptance of alternative types of prosthesis instrument configurations oriented to the research question: “Which product features and process effects determine a high level of employees´ acceptance-to-use?” Materials and methods This study is designed as before-after-comparison based on the usability engineering approach. In the first study phase 46 employees participating in the process of providing instruments for a total knee arthroplasty procedure were queried to examine the current working situation, characterized by using a standard instrumentation set, in terms of instrument handling, work burden, proneness to errors, patient risks, process efficiency and effectiveness. 20 weeks after having implemented a size-specific instrumentation set (second study phase), the same 46 persons were queried on the identical questions. Additionally, learning curve effects were dissected. Results By using standard sets only 30% felt a need for improvement. After 20 weeks only 8% of the employees were satisfied with the former equipment and 69 % regarded the standard set as being relatively prone to error, endangering patient safety. In addition, 85% felt the effectiveness of the standard process is limited. Finally, 75% examined the effectivity of the reengineered process to be significantly higher and 69% stated the reduction of handling disadvantages. Based on these findings an ergonomic decision-making model has been developed. Conclusion Employees’ motivation to use a new technology as a part of an optimized workflow organization is crucial to achieve an enhanced level of effectiveness, efficiency and patient safety. Hence, it is recommended to strengthen change management efforts (e.g. key users to support colleagues, try-out groups for enhancing learning curves) for reducing resistance to change and ensuring the new technology to be successful.